State and Local Pensions : What Now? - Munnell, Alicia Haydock (Book collections on Project MUSE., 2012)
In the wake of the financial crisis and Great Recession, the health of state and local pension plans has emerged as a front burner policy issue. Elected officials, academic experts, and the media alike have pointed to funding shortfalls with alarm, expressing concern that pension promises are unsustainable or will squeeze out other pressing government priorities. A few local governments have even filed for bankruptcy, with pensions cited as a major cause. The author draws on both her practical experience and her research to provide a broad perspective on the challenge of state and local pensions. She shows that the story is big and complicated and cannot be viewed through a narrow prism such as accounting methods or the role of unions. By examining the diversity of the public plan universe, the author debunks the notion that all plans are in trouble. In fact, she finds that while a few plans are in need of fixing, many are functioning reasonably well. The author's analysis concludes that the plans in serious trouble need a major overhaul. But even the relatively healthy plans face three challenges ahead: an excessive concentration of plan assets in equities; the risk that steep benefit cuts for new hires will harm workforce quality; and the constraints plans face in adjusting future benefits for current employees. Here, the author proposes solutions that preserve the main strengths of state and local pensions while promoting needed reforms.